SWOT ANALYSIS IN AN EDUCATIONAL INSTITUTION (Case Study: Baitul Qur'an Islamic Boarding School, Depok) - Gina Rohadatul Aisyi; Lutfi Zulkarnain (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2020)
The development of the educational institution industry continues to increase, which demands an effective marketing strategy to face the increasingly tight competition in the education service business. This research is a qualitative research methodology with a descriptive approach that aims to determine the marketing strategy of Baitul Qur'an educational institutions. The analysis tool used is the analysis of the company's environment (EFE, IFE, and IE Matrix) with the SWOT method (Strength, Weakness, Opportunity, Threat). The results of the Baitul Qur'an Islamic Boarding School evaluation based on Internal and External analysis obtained from the SWOT analysis resulted in an alternative strategy of S-O (Strength-Opportunity). Then, the results of the SWOT analysis are reprocessed using the QSPM (quantitative strategic planning matrix) method to obtain priority strategies from various alternative strategies as well as a decision to choose a strategy. The priority strategy in this study is to optimize the use of digital marketing and other marketing technologies to support the development of Islamic boarding schools in a wider area (6,87).